Kondisi Sosial Ekonomi Keluarga Buruh Pemecah Batu Desa Tambahrejo Pringsewu - Iza Dewi Kartini; Edy Haryono; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2018)
This study was aimed to examine the socio-economic conditions of families of stone breaker in Tambahrejo Village. The method of this research was descriptive with population of 68 people. The data collection techniques were questionnaire and documentation. After collecting the data, the researcher  analyzed the data by spatial or spatial approach. The results of this study indicate that: (1) 64.70% of respondents had hours of working ≥ 40 hours / week with rest 40 hours / week (2) 14.71% of respondents had income ≥ other UMP UMP. (3) 41.17% of respondents had dependents of family members ≥ 5 people had more than 5 people. (4) 1,36% of respondents stated to live in abundance with the expenditure of rice 481-960 Kg/year and the rest declared almost poor and poor. (5) A total of 5.28% of respondent's children are able to continue to Unversity from the total number of respondent's children.Penelitian ini mengkaji tentang kondisi sosial dan ekonomi buruh pemecah batu di Desa Tambahrejo Pringsewu. Penelitian ini menggunakan metode deskriptif dengan jumlah populasi 68 orang. Teknik pengumpulan data yang digunakan yaitu kuesioner dan dokumentasi. Data yang terkumpul kemudian dianalisis dalam pendekatan spasial atau keruangan. Hasil penelitian ini menunjukkan bahwa: (1) sebanyak 64,70 % responden memiliki jam kerja ≥ 40 jam/minggu. (2) Ada 14,71 % responden memiliki pendapatan ≥ UMP. (3) Ada 41,17% responden memiliki tanggungan keluarga ≥ 5 orang. (4) Ada 1,36% responden dikatakan berkehidupan cukup dengan pengeluaran beras 481-960 Kg/Tahun dan sisanya dinyatakan nyaris miskin dan miskin. (5) Ada 5,28% anak responden mampu yang melanjutkan ke Perguruan Tinggi.Kata Kunci: buruh, keadaan sosial ekonomi, pemecah batu